Gypsum heterogenous nucleation pathways regulated by surface functional groups and hydrophobicity - Yan-Fang Guan; Xiang-Yu Hong; Vasiliki Karanikola; Zhangxin Wang; Weiyi Pan; Heng-An Wu; Feng-Chao Wang; Han-Qing Yu; Menachem Elimelech (Nature Communications)
Abstract Gypsum (CaSO4·2H2O) plays a critical role in numerous natural and industrial processes. Nevertheless, the underlying mechanisms governing the formation of gypsum crystals on surfaces with diverse chemical properties remain poorly understood due to a lack of sufficient temporal-spatial resolution. Herein, we use in situ microscopy to investigate the real-time gypsum nucleation on self-assembled monolayers (SAMs) terminated with −CH3, −hybrid (a combination of NH2 and COOH), −COOH, −SO3, −NH3, and −OH functional groups. We report that the rate of gypsum formation is regulated by the surface functional groups and hydrophobicity, in the order of −CH3 > −hybrid > −COOH > −SO3 ≈ − NH3 > − OH. Results based on classical nucleation theory and molecular dynamics simulations reveal that nucleation pathways for hydrophilic surfaces involve surface-induced nucleation, with ion adsorption sites (i.e., functional groups) serving as anchors to facilitate the growth of vertically oriented clusters. Conversely, hydrophobic surfaces involve bulk nucleation with ions near the surface that coalesce into larger horizontal clusters. These findings provide new insights into the spatial and temporal characteristics of gypsum formation on various surfaces and highlight the significance of surface functional groups and hydrophobicity in governing gypsum formation mechanisms, while also acknowledging the possibility of alternative nucleation pathways due to the limitations of experimental techniques.